2015
DOI: 10.4103/2231-4040.157984
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of wound healing activity of Thunbergia laurifolia supercritical carbon dioxide extract in rats with second-degree burn wounds

Abstract: Thunbergia laurifolia Lindl (TL) has been traditionally used as an antidote, anti-inflammatory, and anti-drug addiction. This study investigated the burn wound healing activity of TL leaf extract (TLL) from supercritical CO2 extraction in rats. The extract was prepared to 2.5%, 5%, and 10% gel (TLL gel). Rats were induced to second-degree burn wounds. They were randomly divided into six groups (six rats/group), which five groups were topically applied gel base, 1% silver sulfadiazine gel, 2.5%, 5%, and 10% TLL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Collagen is essential for correct tissue repair and the remodeling of wound skin. 40 Elastic fibers and collagen occur in the reticular dermis, but Masson´s trichrome does not distinguish between these two types of fibers, hence the need to use orcein, which stains elastic fibers a brownish black. 41 The various parameters (a-f listed above) were observed in the control and AgNP-treated groups, but there were no differences in their frequencies between the two groups ( Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…Collagen is essential for correct tissue repair and the remodeling of wound skin. 40 Elastic fibers and collagen occur in the reticular dermis, but Masson´s trichrome does not distinguish between these two types of fibers, hence the need to use orcein, which stains elastic fibers a brownish black. 41 The various parameters (a-f listed above) were observed in the control and AgNP-treated groups, but there were no differences in their frequencies between the two groups ( Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…Thunbergia laurifolia accelerates the healing of burns. One of its constituents, rosmarinic acid, has anti‐inflammatory and analgesic properties (Boonyarikpunchai et al, 2014; Kwansang et al, 2015). The water content of Cucumis sativus is high.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the prior studies, the present study revealed clearly developed epithelization after NAE-8 ® treatment along with irrefutable reductions in the extent of necrosis and inflammatory cell infiltration. Furthermore, NAE-8 ® treatment strongly induced migration of fibroblasts which produce matrix proteins, fibronectin, proteoglycan, hyaluronan, and collagens for wound repair [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…All sections were blindly examined and photographed under a light microscope (Olympus-CX41RF, Olympus Corporation, Tokyo, Japan) by an experienced histologist. Congestion, necrosis, inflammatory cell infiltration, fibroblast proliferation, epithelization, and angiogenesis were scored semiquantitatively and ranked as none, slight, and moderate, as reported by Kwansang et al [ 20 ].…”
Section: Methodsmentioning
confidence: 99%